COUNTRY FOCUS Micro, Small and Medium Enterprises (MSMEs) in Ethiopia - Tulus T.H. Tambunan (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
Definition of Micro, Small and Medium Enterprises (MSMEs) in Ethiopia According to the revised Micro and Small-Scale Enterprises Growth Stages Guideline No.004/2011, the revised definition considers employed labor force including family labor; total assets without working building and the division of sub sector in to service and industry are the main criteria. The industrial sector includes manufacturing, construction and mining sub sectors, and the service sector includes retail trade, transport, hotel and tourism, information technology and repairs. According to the previous definition, a micro and small enterprise (MSE) in industry was a business enterprise which employs not more than five labor force including business owner and family labor and/or the monetary value of the enterprise’s total asset is not more than 100000 Ethiopian Birr (ETB). In the service sector, a MSE was an enterprise which employs not more than five labor force including business owner and family labor and/or the monetary value of the enterprise’s total asset is not more than 50000 ETB.